Biblical language instruction by the book: Rethinking the status quaestionis. - Sanders, Carl E. (Teaching Theology & Religion, 2017)
Grammar-translation pedagogy is the standard for biblical language instruction. Second language acquisition scholars have argued that grammar-translation is ineffective and not empirically justified. Moreover, evidence suggests most seminary graduates do not use biblical languages effectively in ministry. Task-based instruction is an important alternative pedagogy which focuses on the tasks students will be using the language for and designs the curriculum around those tasks. A task-based approach de-emphasizes translation and memorization of forms. Instead, the emphasis from the beginning is on biblical interpretation and exposition. Available software based resources offer new possibilities for task-based teaching, as students can identify forms and vocabulary and have access to a library of resources. A task-based pedagogy using these tools enables students to quickly develop skills in biblical interpretation that are normally reserved for the third or fourth semester of study. Task-based pedagogy offers great promise for effective and efficient biblical language pedagogy.